Design chains a handbook for integrated collaborative design - Austin, S. A. (Thomas Telford, 2001)
The practices developed through the Integrated Collaborative Design Project (ICD) & described here provide a timely response to the need to manage design complexity to help collaborating organisations deliver projects that meet client needs.